Genetic structure of populations of whale sharks among ocean basins and evidence for their historic rise and recent decline. Issue 10 (May 2014) - Vignaud, Thomas M.; Maynard, Jeffrey A.; Leblois, Raphael; Meekan, Mark G.; Vázquez‐Juárez, Ricardo; Ramírez‐Macías, Dení; Pierce, Simon J.; Rowat, David; Berumen, Michael L.; Beeravolu, Champak; Baksay, Sandra; Planes, Serge
Abstract This study presents genetic evidence that whale sharks, Rhincodon typus, are comprised of at least two populations that rarely mix and is the first to document a population expansion. Relatively high genetic structure is found when comparing sharks from the Gulf of Mexico with sharks from the Indo‐Pacific. If mixing occurs between the Indian and Atlantic Oceans, it is not sufficient to counter genetic drift. This suggests whale sharks are not all part of a single global metapopulation. The significant population expansion we found was indicated by both microsatellite and mitochondrial DNA. The expansion may have happened during the Holocene, when tropical species could expand their range due to sea‐level rise, eliminating dispersal barriers and increasing plankton productivity. However, the historic trend of population increase may have reversed recently. Declines in genetic diversity are found for 6 consecutive years at Ningaloo Reef in Australia. The declines in genetic diversity being seen now in Australia may be due to commercial‐scale harvesting of whale sharks and collision with boats in past decades in other countries in the Indo‐Pacific. The study findings have implications for models of population connectivity for whale sharks and advocate for continued focus on effective protection of the world's largest fish at multiple spatial scales.